Risk Factors Analysis of Diaper Dermatitis in Children Aged 0-36 Months at Puskesmas Working Area, Tembalang District - Ika Dyah Kurniati; Laila Arina Hukma Adila; Retno Indrastiti (Universitas Ahmad Dahlan, 2023)
Diaper dermatitis is an inflammation of the skin in the diaper area caused by contact with urine and feces and the friction of the diaper against the skin. The incidence of diaper dermatitis in Indonesia is 7-35% in male and female infants with the highest number at the age of 6-12 months. The purpose of this study was to determine the factors associated with diaper dermatitis in children aged 0-36 months at the Tembalang District Puskesmas, such as age, gender, mother's education level, mother's occupation, economic status, frequency of diaper changes, and personal hygiene. This study used an observational analytic method of Case-Control approach with a sample of 30 people, 15 case groups and 15 control groups with purposive sampling technique. Data were obtained through a questionnaire instrument which was then tested with the Chi-Square test with the help of software. Statistical test results showed no significant relationship between age, gender, mother's education level, mother's occupation, and economic status with the occurrence of diaper dermatitis and there was a significant relationship between the frequency of diaper changes 0.013 (p < 0.05) and personal hygiene 0.008 (p < 0.05). There is a significant relationship between the frequency of diaper changes and personal hygiene with the occurrence of diaper dermatitis, and there is no significant relationship with other risk factors.